Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1152/japplphysiol.00005.2003
|View full text |Cite
|
Sign up to set email alerts
|

M1/70 attenuates blood-borne neutrophil oxidants, activation, and myofiber damage following stretch injury

Abstract: The purpose of this study was to determine the role of the CD11b-dependent respiratory burst in neutrophil oxidant generation and activation, interleukin-8 (IL-8) production, and myofiber damage after muscle stretch injury by using the monoclonal antibody M1/70 to block this pathway. Twelve male New Zealand White rabbits were randomly assigned to a treatment group: M1/70 (n = 6), IgG isotype control (n = 3), or saline control (n = 3). After intravenous injection of the assigned agent under gas anesthesia, a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 55 publications
2
48
0
Order By: Relevance
“…The observation that CD18−/− mice are protected from contraction-induced muscle injury and oxidative damage in the present study are in agreement with Brickson et al (2003) who reported that the administration of a blocking antibody for neutrophils reduced histological signs of muscle injury in rabbits 24 h after a single lengthening contraction. On the other hand, Lowe et al (1995) reported that neutrophils do not cause muscle injury after lengthening contractions based on observations made after administering a blocking antibody for neutrophils.…”
Section: Csa (Um 2 )supporting
confidence: 94%
“…The observation that CD18−/− mice are protected from contraction-induced muscle injury and oxidative damage in the present study are in agreement with Brickson et al (2003) who reported that the administration of a blocking antibody for neutrophils reduced histological signs of muscle injury in rabbits 24 h after a single lengthening contraction. On the other hand, Lowe et al (1995) reported that neutrophils do not cause muscle injury after lengthening contractions based on observations made after administering a blocking antibody for neutrophils.…”
Section: Csa (Um 2 )supporting
confidence: 94%
“…For example, muscle injury following a puncture wound with a needle was reduced by administration of functionblocking, soluble CD11b or antibodies to CD11b prior to needle puncture, and the reduced injury was accompanied by a reduction in neutrophils entering the damaged tissue (138). Similarly, systemic administration of function-blocking, antiCD11b before applying mechanical injury to muscle was sufficient to reduce muscle fiber damage (10). Thus, reductions of central nucleation in muscle fibers following injury of phagocyte-depleted mice may reflect both reductions in phagocyte-mediated damage and impaired regenerative capacity caused by slower removal of cellular debris.…”
Section: Do Neutrophils or M1 Macrophages Promote Muscle Regenerationmentioning
confidence: 99%
“…Neutrophils are the first inflammatory cells to infiltrate the injured muscle, with a significant increase in their numbers as early as 1-6 h after myotoxin-or exercise-induced muscle damage (Orimo et al 1991;Fielding et al 1993). Some reports revealed that prevention of neutrophil infiltration after injury reduces force deficits and histological damage to muscle fibers (Walden et al 1990;Brickson et al 2003;Pizza et al 2005;Lockhart and Brooks 2008), suggesting that neutrophils contribute to muscle fiber damage. In the present study, although neutrophils did not show a correlation with degenerating myofibers, a negative correlation with regenerated myofibers was noted, indicating that neutrophils decrease with progression of regeneration.…”
Section: Discussionmentioning
confidence: 99%